Bone volume change following vascularized free bone flap reconstruction of the mandible. Issue 9 (September 2020) - Ritschl, Lucas M.; Fichter, Andreas M.; Grill, Florian D.; Hart, Diandra; Hapfelmeier, Alexander; Deppe, Herbert; Hedderich, Dennis M.; Wolff, Klaus-Dietrich; Mücke, Thomas
Abstract: Background: Bone volume changes following vascularized bone flaps and possible confounding factors over time are described in the literature with some controversy. The purpose of this study was to evaluate the bone volume behavior of two frequently used free flaps. Materials and methods: Computed tomography (CT) scans were examined with regard to bone volume using the software program ITK-SNAP for all patients who required mandibular reconstruction with a free fibula flap (FFF, conventionally vs assisted by computer-aided design/computer-aided manufacturing (CAD/CAM)) or iliac crest flap (DCIA) following mandibular resection because of benign or malign processes, between August 2010 and August 2015. Clinical data, complication rates, and CT scans were analyzed retrospectively. Additionally, complication rates (microvascular revision, flap loss, postoperative fistula or dehiscence, and postoperative bone exposure) were compared within early (≤30 days), late (31st–100th day), and overall (≤100th day) postoperative time intervals. Results: 113 cases, comprizing 89 FFF and 24 DCIA cases, were included. FFF showed superior bone volume behavior over the DCIA flap. Multivariable regression models assessed the relationships between the following and bone volume behavior: interval between operation and CT scan ( p  < 0.683), age ( p  = 0.004), gender ( p  = 0.006), BMI ( p  = 0.400), adjuvant radiation therapy ( p  = 0.334), reconstruction with DCIA flap ( p  < 0.0001), number of segments ( p  = 0.02), and incidence of dental implant insertion ( p  = 0.45). Conclusions: The bone volume of FFFs remains stable. DCIA flaps show a higher bone volume reduction, but the postoperative course might be associated with fewer complications. Time interval between operation and CT scan, age, gender, reconstruction with DCIA flap, and number of fibula segments contributed significantly to bone volume behavior.